Outcomes of synchronous systemic and central nervous system (CNS) involvement of diffuse large B‐cell lymphoma are dictated by the CNS disease: a collaborative study of the Australasian Lymphoma Alliance. (24th June 2019) - Wight, Joel C.; Yue, Mimi; Keane, Colm; Johnston, Anna; Linton, Kim; Chin, Collin; Wai, Shin Hnin; Talaulikar, Dipti; Gasiorowski, Robin; Cheah, Chan Yoon; Gregory, Gareth P.; Dickinson, Michael; et al.
Summary: De novo diffuse large B‐cell lymphoma (DLBCL) presenting with synchronous central nervous system (CNS) and systemic disease (synDLBCL) is not well described and is excluded from clinical trials. We performed a retrospective analysis of 80 synDLBCL patients treated across 10 Australian and UK centres. Of these patients, 96% had extranodal systemic disease. CNS‐directed treatment with combination intravenous cytarabine and high‐dose methotrexate ("CNS‐intensive") ( n = 38) was associated with favourable survival outcomes compared with "CNS‐conservative" strategies such as intravenous high‐dose methotrexate monotherapy, intrathecal therapy and/or radiotherapy (2‐year progression‐free survival [PFS] 50% vs. 31%, P = 0·006; 2‐year overall survival [OS] 54% vs. 44%, P = 0·037). Outcomes were primarily dictated by the ability to control the CNS disease, with 2‐year cumulative CNS relapse incidence of 42% and non‐CNS relapse 21%. Two‐year OS for CNS‐relapse patients was 13% vs. 36% for non‐CNS relapses ( P = 0·02). Autologous stem cell transplantation as consolidation ( n = 14) was not observed to improve survival in those patients who received CNS‐intensive induction when matched for induction outcomes (2‐year PFS 69% vs. 56%, P = 0·99; 2‐year OS 66% vs. 56%, P = 0·98). Hyperfractionated or infusional systemic treatment did not improve survival compared to R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) (2‐year OS 49% for both groups). Our study suggests that adequate control of the CNS disease is paramount and is best achieved by intensive CNS‐directed induction.